Leprosy: Comprehensive insights into pathology, immunology, and cutting-edge treatment strategies, integrating nanoparticles and ethnomedicinal plants - Kimta, Neetika; Majdalawieh, Amin F.; Nasrallah, Gheyath K.; Puri, Sunil; Nepovimova, Eugenie; Jomova, Klaudia; Kuča, Kamil (Frontiers in Pharmacology, 2024)
Mycobacterium leprae is the causative agent responsible for the chronic disease known as leprosy. This condition is characterized by dermal involvement, often leading to peripheral nerve damage, sensory-motor loss, and related abnormalities. Both innate and acquired immunological responses play a role in the disease, and even in individuals with lepromatous leprosy, there can be a transient increase in T cell immunity during lepromatous reactions. Diagnosing of earlystage leprosy poses significant challenges. In this context, nanoparticles have emerged as a promising avenue for addressing various crucial issues related to leprosy. These include combatting drug resistance, mitigating adverse effects of conventional medications, and enhancing targeted drug delivery. This review serves as a comprehensive compilation, encompassing aspects of pathology, immunology, and adverse effects of multidrug delivery systems in the context of leprosy treatment. Furthermore, the review underscores the significance of ethnomedicinal plants, bioactive secondary metabolites, and nanotherapeutics in the management of leprosy. It emphasizes the potential to bridge the gap between existing literature and ongoing research efforts, with a profound scope for validating traditional claims, developing herbal medicines, and formulating nanoscale drug delivery systems that are safe, effective, and widely accepted.